2016
DOI: 10.1111/fcre.12246
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Satisfaction, and Settlement in Domestic Relations Mediations: New Findings

Abstract: Researchers and mediators have long been concerned about coercion, intimidation, and safety threats that could occur in mediation for cases where previous violence between the parties has occurred. Most of the research focuses on screening tools to identify parties at risk. When parties screen positive for intimate partner violence (IPV), some proceed to mediation and some do not, depending on the policies of individual mediation programs. But this misses a step: Some cases may benefit from mediation while oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Specifically, scholarship has discussed concerns over IPV screening (or lack of screening), mediation procedures to be used in cases of IPV, safety of victims during and after mediation, and safety regarding the terms of agreements. There is also scholarship that investigates satisfaction rates of mediation clients who report and who do not report IPV (Raines, Choi, Johnson, & Coker, 2016).…”
Section: Research Studymentioning
confidence: 99%
“…Specifically, scholarship has discussed concerns over IPV screening (or lack of screening), mediation procedures to be used in cases of IPV, safety of victims during and after mediation, and safety regarding the terms of agreements. There is also scholarship that investigates satisfaction rates of mediation clients who report and who do not report IPV (Raines, Choi, Johnson, & Coker, 2016).…”
Section: Research Studymentioning
confidence: 99%
“…Mediation has become a standard way that divorces are handled in the USA (Raines et al , 2016), particularly in jurisdictions (such as those analyzed for this paper), where mediation is required prior to any hearing involving a judge. Mayer (2013) suggests this mandate was made to create a better process and outcome for the parties.…”
Section: Family Law Mediationmentioning
confidence: 99%
“…The presence of IPV/A clearly impacts and reduces the rates of settlement in mediation (Raines et al, ). Kelly () and Beck et al () both found that high levels of conflict predicted lower mediation settlement rates.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the relatively early days of divorce and family mediation, back in the 1980's and early 1990's, many domestic violence (DV) advocates were concerned that mediation would lead to unfair and coerced agreements (Pearson & Thoennes, ; Steegh & Dalton, ). In the intervening decades, mediation has become commonplace even in cases where allegations of domestic abuse exist (Raines, Choi, Johnson, & Coker, ). Yet many of the critical assumptions underlying concerns surrounding domestic violence and mediation have not been empirically tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation